Self-Employment Dynamics, State Dependence and Cross-Mobility Patterns - Marco Caliendo; Arne Uhlendorff (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
This paper analyzes the mobility between self-employment, wage employment and non-employment. Using data for men in West Germany, we find strong true state dependence in all three states. Moreover, compared to wage employment, non-employment increases the probability of self-employment significantly, and selfemployment goes along with a higher risk of future non-employment.
Keywords: J64; L26; C23; C25; 330; Self-Employment; State Dependence; Labor Market Dynamics; Unemployment